Control system response for seed placement accuracy on row crop planters - Badua, Sylvester Alfredo (Kansas State University, 2020)
Planting is one of the most critical field operations that can highly influence early season vigor, final plant density and ultimately potential crop yield. It is the opportunity to place seeds at a uniform depth and spacing providing them the ideal environment for proper growth and development. However, inherent field spatial variability could influence seed placement and requires proper implementation of planter settings to prevent shallow seeding depth, sidewall compaction and uneven spacing. The overall goal of this research is to evaluate the response of the planter and crop to downforce control system implementation across a wide range of machine and field operating conditions. Planting operations were performed in corn production fields using a Horsch row-crop planter with 12 row units equipped with a hydraulic downforce system capable of implementing fixed and active downforce settings. A custom-made data acquisition system was developed to record sensor data at 10 Hz sampling frequency. From this study, the following conclusions were drawn. First, soil texture and soil compaction due to tractor tires influenced real-time gauge wheel load (GWL). Implementing a fixed downforce setting with target GWL set at 35 kg showed that 25% of the total planting time GWL was less than 0 suggesting areas planted with uncertain seeding depth due to potential loss of ground contact of the gauge wheels. Likewise, fewer row units per section could provide lower variability in GWL indicating the need for an automatic section control to maintain target GWL within an acceptable range for all row units. Second, implementing an active downforce setting showed no significant difference between downforce A (63 kg) and downforce B (100 kg) on plant spacing, although downforce setting B resulted to higher plant spacing accuracy. Higher variability in spacing was observed when ground speed is over 12 kph. To achieve desired seeding depth, downforce greater than 100 kg is needed when ground speed is over 7.2 kph on no-till field and when ground speed is over 12 kph on strip-tilled field. Third, response of row units segregated in sections revealed that row unit acceleration on wing, track and non-track sections increases with speed. Strip-tilled soil exhibited lower row unit acceleration by 18% compared to no-till soil. Finally, a proof-of-concept sensing and measurement (SAM) system was developed to calculate seed spacing, depth and geo-location of corn. This system could provide real-time feedback on seed spacing and depth allowing appropriate downforce control system management for more consistent seed placement during planting. In summary, advances in planter technology paved the way for the addition of more row units across on the planter to increase planting productivity. With increasing width of planter toolbar, each row unit may need different downforce control to varying field and machine operating conditions. Appropriate downforce control management should be implemented to compensate for increased dynamics of planter row units across a highly variable field conditions to achieve the desired seed placement accuracy.
Keywords: Control system; Planter downforce; Uniform seed placement; Gauge wheel load